A Bibliometric Analysis of Islamic Law and Philosophy: Global Trends, Key Participants, and Developing Themes - Md. Ziaur Rahman; Mahmudulhassan; Ardiansyah; Usman Aliyu Yunusa (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study maps the bibliometric landscape of the study of Islamic philosophy, law, and law for the period 2019–2024 with a focus on themes, influential figures, publication trends, and the interconnectedness of philosophy of law, ethics, and human rights in global discourse. Theoretical framework: This study uses bibliometric approaches and scientific communication theory to analyze patterns of publication, collaboration, and cross-disciplinary knowledge development. Literature review: Previous studies have shown interdisciplinary trends in Islamic philosophy, law, and economics, but not many have examined the connection between the three simultaneously. Methods: Data obtained from Scopus using a Boolean search. Of the 14,632 articles, 185 were selected for analysis with Microsoft Excel, R-Studio, and VOSViewer, covering publication trends, collaborations, institutional contributions, and keyword co-occurrence. Results: Publications peaked in 2021 and then declined. Major contributors are from the US, UK, and Indonesia. The analysis shows the close linkage between ethics, philosophy, and law with a multidisciplinary character, as well as identifying key academics and institutions. Implications: A study of the post-2021 productivity decline and increased international collaboration, especially from underrepresented regions, is needed. Novelty: This research is the first comprehensive mapping that integrates Islamic philosophy, law, and law (2019–2024), affirms multidisciplinary interconnectedness, and places Indonesia as an important actor in global academic discourse.